eduroam in Africa - Fiore, Silvia; Dekkar, Leila; Aseda, Kennedy (IST-Africa Institute and IIMC, 2023)
eduroam is the secure, worldwide roaming access service developed for the international research and education community to address the increasing need for fast and secure Internet connection everywhere. With over 6.4 billion international authentications to date stretching across 106 countries, eduroam is expanding in Africa, where National Research and Education Networks (NRENs) are going beyond the traditional campus connectivity aiming at bridging the digital divide. Uganda, South Africa and Kenya are leading the way and connecting users off campus at bus stops, libraries, cafes, and hospitals. NRENs are at the helm of Africa’s digital transformation and eduroam is a tangible solution to bridging the digital divide. This paper is, therefore, a guidebook detailing the technology behind eduroam, the benefits and the challenges for its four main target groups in Africa: users, institutions, NRENs and municipalities. The call for action is to further deploy eduroam hotspots and provide connectivity everywhere on the continent, including remote areas and unprivileged communities where students, researchers and teachers are present.
Keywords: AfricaConnect; AfricaConnect2; AfricaConnect3; Internet Connectivity; Research and Education Community; NRENs; eduroam; digital divide; inclusion; ICT4D; eduGAIN; roaming; students; authentication; federation; e-learning; COVID- 19